Proton-Coupled Electron Transfer Originating from Excited States of Luminescent Transition-Metal Complexes - Wenger, Oliver S. (Chemistry : a European journal, 2011)
Proton‐coupled electron transfer (PCET) is of fundamental importance for small‐molecule activation processes, such as water splitting, CO2‐reduction, or nitrogen fixation. Ideally, energy‐rich molecules such as H2, CH3OH, or NH3 could be generated artificially using (solar) light as an energy input. In this context, PCETs originating directly from electronically excited states play a crucial role. A variety of transition‐metal complexes have been used recently for fundamental investigations of this important class of reactions, and the key findings of these studies are reviewed in this article. The present minireview differs from other reviews on the subject of PCET in that it focuses specifically on reactions occurring directly from electronically excited states. Electron transfer revisited! Proton‐coupled electron transfer (PCET) is a key process in natural photosynthesis and nitrogen fixation. For artificial photosynthesis, PCET reactions originating directly from electronically excited states are particularly important. Recent fundamental investigations of this important class of reactions are reviewed.